2022
DOI: 10.3390/antibiotics11070837
|View full text |Cite
|
Sign up to set email alerts
|

Association between Augmented Renal Clearance and Inadequate Vancomycin Pharmacokinetic/Pharmacodynamic Targets in Chinese Adult Patients: A Prospective Observational Study

Abstract: This study aimed to examine the risk factors of augmented renal clearance (ARC) and the association between ARC and vancomycin pharmacokinetic/pharmacodynamic (PK/PD) indices in Chinese adult patients. A prospective, observational, multicenter study was conducted, and 414 adult patients undergoing vancomycin therapeutic drug monitoring (TDM) were enrolled. Clinical and PK/PD data were compared between ARC and non-ARC groups. Independent risk factors were examined using a multivariate logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In contrast to earlier findings, researchers could not confirm that ARC occurred more often in males[30]. Moreover, Zhao et al identified risk factors associated with ARC in Chinese adult patients, which included the male gender, age < 50 years, overweight, receiving mechanical ventilation, enteral nutrition, neutrophil percentage, and cardiovascular diseases[31].…”
mentioning
confidence: 76%
“…In contrast to earlier findings, researchers could not confirm that ARC occurred more often in males[30]. Moreover, Zhao et al identified risk factors associated with ARC in Chinese adult patients, which included the male gender, age < 50 years, overweight, receiving mechanical ventilation, enteral nutrition, neutrophil percentage, and cardiovascular diseases[31].…”
mentioning
confidence: 76%
“…In the vast majority of the included studies, critically ill patients were compared based on the presence or absence of ARC. ARC prevalence among these patients ranged from 16.4% to 72% [10,18,19,[22][23][24][25][26][27]. The comparisons consistently revealed that younger age, male sex, heavier weight, lower illness severity, and the presence of brain injury or trauma were the factors most frequently linked with a higher risk for ARC.…”
Section: Arc Definition and Its Prevalencementioning
confidence: 88%
“…The comparisons consistently revealed that younger age, male sex, heavier weight, lower illness severity, and the presence of brain injury or trauma were the factors most frequently linked with a higher risk for ARC. Other associated factors could be receiving mechanical ventilation, enteral nutrition, hemodynamic instability, low serum albumin, low platelet count, low serum creatinine, high glomerular filtration rate, presence of TBI, febrile neutropenia, trauma, intracerebral hemorrhage, and aneurysmal subarachnoid hemorrhage [20,23,26,28]. Furthermore, Zhao J et al [26] conducted a study that aimed to evaluate two widely used scoring systems (ARCTIC and ARC risk scoring) to help define high ARC risk factors, revealing that 58.9% of ARC patients had high-risk scores when assessed in the ICU, while 88.9% had high-risk scores among trauma patients.…”
Section: Arc Definition and Its Prevalencementioning
confidence: 99%
“…Previous studies have observed that patients with ARC have insufficient therapeutic concentrations of antibiotics; therefore, these patients are at a high risk of treatment failure. Inadequate therapeutic concentrations are more likely associated with antibiotics that undergo renal elimination (Chen and Nicolau, 2020;Zhao et al, 2022). Chu et al conducted a retrospective study in patients receiving vancomycin at dose of 1,000 mg every 12 h. The trough of vancomycin then measured and they observed that vancomycin trough concentrations were lower than the minimum recommended range in 62.9% of patients who showed ARC.…”
Section: Introductionmentioning
confidence: 99%